2015
DOI: 10.1128/aac.04442-14
|View full text |Cite
|
Sign up to set email alerts
|

War Wound Treatment Complications Due to Transfer of an IncN Plasmid Harboring bla OXA-181 from Morganella morganii to CTX-M-27-Producing Sequence Type 131 Escherichia coli

Abstract: A 22-year-old male developed a recurrent sacral abscess associated with embedded shrapnel following a blast injury. Cultures grew extended-spectrum ␤-lactamase (ESBL)-producing, carbapenem-susceptible Escherichia coli. Ertapenem was administered, but the infection recurred after each course of antibiotics. Initial surgical interventions were unsuccessful, and subsequent cultures yielded E. coli and Morganella morganii, both nonsusceptible to carbapenems. The isolates were Carba NP test negative, gave ambiguous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…We selected all of the CTX-M-27 producers, 1 CTX-M-14 producer per country, and 2 CTX-M-15 producers. We also sought public databases for ST131 H 30 and included sequence data for 8 isolates from countries other than Japan: CTX-M-27 producers (3 raw reads, 2 draft genomes); CTX-M-14 producer (1 raw read); and CTX-M-15–producing C2/ H 30Rx (2 complete genomes) (Table; Technical Appendix Table 1) ( 5 , 9 , 16 18 ). …”
Section: Methodsmentioning
confidence: 99%
“…We selected all of the CTX-M-27 producers, 1 CTX-M-14 producer per country, and 2 CTX-M-15 producers. We also sought public databases for ST131 H 30 and included sequence data for 8 isolates from countries other than Japan: CTX-M-27 producers (3 raw reads, 2 draft genomes); CTX-M-14 producer (1 raw read); and CTX-M-15–producing C2/ H 30Rx (2 complete genomes) (Table; Technical Appendix Table 1) ( 5 , 9 , 16 18 ). …”
Section: Methodsmentioning
confidence: 99%
“…The PCR scheme was complemented with primers specific for the IncX3-type plasmid backbones (IncX3 Fw, 5=-GAG GCT TAT CGT GAA GAC AG-3=; IncX3 Rv, 5=-GAA CGA CTT TGT CAA ACT CC-3=) (13), as well as primers specific for IncX4 plasmids (39). The genetic environment of bla OXA-181 was investigated by PCR mapping with primers for insertion sequences ISKpn19 and IS3000, taking in account that those mobile elements have been previously identified in the close vicinity of the bla OXA-181 gene (7,40).…”
Section: Methodsmentioning
confidence: 99%
“…Although K. pneumoniae is most commonly found in soil and water, it frequently causes infections in immunocompromised individuals and has been connected to outbreaks of nosocomial infections (Podschun & Ullmann, 1998;Paczosa & Mecsas, 2016;Navon-Venezia et al, 2017). OXA-163 and OXA-181 have also been identified in other human pathogens such as Escherichia coli (McGann et al, 2015;Stoesser et al, 2016), and OXA-181 has been identified in Pseudomonas aeruginosa strains (Meunier et al, 2016). OXA-181 is reported to originate from a Shewanella xiamenensis chromosomal -lactamase and OXA-163 also appears to originate from Shewanella.…”
Section: Introductionmentioning
confidence: 99%